Chronic Mesenteric Ischemia: 20 Year Experience of Open Surgical Treatment. Issue 5 (May 2015) - Lejay, A.; Georg, Y.; Tartaglia, E.; Creton, O.; Lucereau, B.; Thaveau, F.; Geny, B.; Chakfe, N.
Abstract : Objectives: Both open surgery (OS) and endovascular surgery (ES) have been proposed for the treatment of symptomatic chronic mesenteric ischaemia (CMI). OS was considered the gold standard but ES is increasingly proposed as the first option. The aim was to report long-term outcomes associated with OS in patients suffering CMI in the modern era in order to help in choose between the two techniques. Materials and methods: A retrospective single centre analysis of all consecutive digestive artery revascularizations performed for CMI between January 2003 and December 2012 was carried out. Primary outcomes were 30 day mortality and morbidity, and secondary outcomes were survival, primary patency (PP), secondary patency (SP), and freedom from digestive symptoms, depending on the completeness of the revascularization performed. Results: Eighty-six revascularizations were performed. Median follow up was 6.9 years (range 0.3–20.0). The 30 day mortality and morbidity rates were respectively 3.5% and 13.9%. Ten year survival was 88% for complete revascularization (CR) and 76% for incomplete revascularization (IR) ( p = .54). The PP was 84% at 10 years for CR and 87% respectively for IR ( p = .51). The 10 year SP was 92% for CR and 93% for IR ( p = .63). Freedom from digestive symptoms was influenced by the completeness of revascularization: 79% for CR versus 65% for IR at 10 years ( p = .04). Conclusions: OS for CMI, especially complete revascularization, provides lasting results despite high morbidity.